2010
DOI: 10.1016/j.canlet.2009.06.038
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological NFκB inhibitors BAY117082 and MG132 induce cell arrest and apoptosis in leukemia cells through ROS-mitochondria pathway activation

Abstract: A growing body of evidence suggests the inhibition of NFkappaB as a strategy to induce cell death in tumor cells. In this work, we evaluated the effects of the pharmacological NFkappaB inhibitors BAY117082 and MG132 on leukemia cells apoptosis. BAY117082 and MG132 presented potent apoptotic effects compared to inhibitors of MAPKs, EGFR, PI3K/Akt, PKC and PKA signaling pathways. Non-tumor peripheral blood cells were insensitive to BAY117082 and MG132 apoptotic effects. BAY117082 and MG132-induced apoptosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 37 publications
6
29
1
Order By: Relevance
“…This suggests that induction of ROS and subsequently Nrf2 nuclear accumulation in monocytes are independent of NF-kB activation. Moreover, blocking NF-kB activity alone or in combination with TNF has been shown to increase the levels of ROS, which can induce apoptosis (21,30,31). In this study, no apoptosis was observed in human monocytes by the treatment of NF-kB inhibition.…”
Section: Discussionmentioning
confidence: 50%
“…This suggests that induction of ROS and subsequently Nrf2 nuclear accumulation in monocytes are independent of NF-kB activation. Moreover, blocking NF-kB activity alone or in combination with TNF has been shown to increase the levels of ROS, which can induce apoptosis (21,30,31). In this study, no apoptosis was observed in human monocytes by the treatment of NF-kB inhibition.…”
Section: Discussionmentioning
confidence: 50%
“…Likewise, abrogating TLR2/PI3K/Akt-dependent mechanisms by inhibition with LY294002 failed to protect cardiomyocytes against doxorubicin-induced cardiomyopathy [83] and brain cells against ischemic injury [84]. Our results demonstrate that NF-κB or PI3K inhibition showed a dose-dependent cytotoxic effect on ALL cells, consistent with reports that both pathways contribute to the survival advantage of leukemic blasts [85,86]. Based on our results, it appears that NF-κB and PI3K suppress proapoptotic signals generated by Pam 2 CSK 4 through simultaneous induction of prosurvival pathways, and still have the capacity to dampen the full extent of Pam 3 CSK 4 -mediated apoptosis in ALL cells, as their inhibition at concentrations that do not induce relevant cytotoxicity on their own augmented Pam 3 CSK 4 -mediated cell death and transformed Pam 2 CSK 4 into a cell-death inducing agent.…”
supporting
confidence: 88%
“…NFκB is bound to the inhibitory protein IκB, which retains NFêB within the cytosol thus preventing its transcriptional activity. Bay 11-7082 inhibits IKK and parthenolide inhibits NFκB, effects considered to contribute to their negative effect on cell survival [7]. Considering the restricted specifity of Bay 11-7082 and parthenolide [8,9,[44][45][46], and the lack of an inhibitory effect of Bay 11-7082 on the phosphorylation status of IκB-α, the pharmacological evidence in favour of a functional role for NFκB in the regulation of erythrocyte survival is limited.…”
Section: Discussionmentioning
confidence: 99%
“…IκB 46 phosphorylation by IκB kinase (IKK) prepares IκB for ubiquitination and subsequent degradation. Pharmacological inhibition of IKK by Bay 11-7082 or of NFκB by parthenolide trigger apoptosis [4][5][6][7]. Beyond that, the substances may in addition compromize cell function and survival by interference with NFκB-independent mechanisms, such as caspase 1 [8,9].…”
Section: Introductionmentioning
confidence: 99%